Comparison of the Length-Size Structure of the Glass Eels Anguilla Bicolor Bicolor in the Cikaso Estuary and River Areas, Sukabumi, Indonesia - Baihaqi, Faqih; Annida, Shafira Bilqis (PT FORMOSA CENDEKIA GLOBAL, 2025)
Cikaso is one of several areas in Sukabumi Regency has the highest glass eel catch production. Glass eel catch in the Cikaso area occurs in two areas, around the estuary and river. One of the most dominant glass eel catch species is Anguilla bicolor bicolor. This study compared the length structure of glass eels A. bicolor bicolor caught in the Cikaso Estuary and River areas. Glass eels were caught using a push net with a mesh size of 0.48 mm every month from December 2020 to April 2021. The study revealed that the average length of glass eels A. bicolor bicolor, caught in the river area, was longer (98.0 mm) than those caught in the estuary area (91.2 mm). This is thought to be due to growth factors and the natural selection of glass eels A. bicolor bicolor during their movement in the recruitment process to the Cikaso River area.